IMPLEMENTASI ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN PELAYANAN INFORMASI DI SMPN 17 TANGERANG - Wahyuntari, Arintya; Hasugian, Humisar; Wulandari, Wulandari; Nofiyani, Nofiyani (Universitas Budi Luhur, 2024)
17 Tangerang Junior High School is one of the first high schools that prioritizes the management of good relationships to increase the satisfaction of optimal service between the school and the parents of students. However, there is a problem faced by 17 Tangerang Junior High School that the delivery of school information is still manual with the use of letters of instruction and it is not effective to handle parents' complaints related to the services provided by the school. In solving the problem, one of the information technology approaches is to create an Electronic Customer Relationship Management (e-CRM) website with the Enhance phase. The study was designed using the waterfall method. The system is generated using PHP, HTML, CSS, Visual Studios Code and Node.js as programming languages and on database design using MySQL. The result of this research is an e-CRM system that can improve the information service in 17 Tangerang Junior High School which can be used by the parents of students to learn information quickly, making it easier for the school, especially the classmaster, to deliver invitation letters to the students' parents as well as to communicate criticism and advice related to the service provided by the school.